The way home - Leather sue (John F.); Butler, Shakti; Butler, Rick.; Gosling, Maureen; World Trust (Organization) (cambridge : Cambridge University Press : Open University, 2008)
Over the course of eight months, 64 women come together to share their experiences of oppression through the lens of race. Separated into eight ethnic councils, Indigenous, African-American, Arab, Asian, European-American, Jewish, Latina, and Multiracial, the women explore their stories of identity, oppression, and resistance.
Originally produced in 1998.
UNCW copy does not include a guide.
Cinematographer, Rick Butler; Editor, Maureen Gosling; Animation/Graphics, Deborah Miller.
VHS.
Keywords: Sex discrimination against women -- United States; Race discrimination -- United States; Women -- United States -- Social conditions; Oppression (Psychology).